Overwintering of Sclerotium rolfsii and S. rolfsii var. delphinii in Different Latitudes of the United States - Xu, Z (Plant disease, 2008)
Previously known only from the southern United States, hosta petiole rot recently appeared in the northern United States. Sclerotium rolfsii var. delphinii is believed to be the predominant petiole rot pathogen in the northern United States, whereas S. rolfsii is most prevalent in the southern United States. In order to test the hypothesis that different tolerance to climate extremes affects the geographic distribution of these fungi, the survival of S. rolfsii and S. rolfsii var. delphinii in the northern and southeastern United States was investigated. At each of four locations, nylon screen bags containing sclerotia were placed on the surface of bare soil and at 20-cm depth. Sclerotia were recovered six times from November 2005 to July 2006 in North Dakota and Iowa, and from December 2005 to August 2006 in North Carolina and Georgia. Survival was estimated by quantifying percentage of sclerotium survival on carrot agar. Sclerotia of S. rolfsii var. delphinii survived until at least late July in all four states. In contrast, no S. rolfsii sclerotia survived until June in North Dakota or Iowa, whereas 18.5% survived until August in North Carolina and 10.3% survived in Georgia. The results suggest that inability to tolerate low temperature extremes limits the northern range of S. rolfsii